Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
17x + 3. ( -16x – 37) = 2x + 43 - 4x
<=>17x-48x-111=-2x+43
<=>-29x=154
<=> \(x=-\frac{154}{29}\)
-3. (2x + 5) -16 < -4. (3 – 2x)
\(\Leftrightarrow-6x-31< -12+8x.\)
\(\Leftrightarrow-14x< 19\Rightarrow x< -\frac{19}{14}\)
Câu 1:
a: =>-2x-x+17=34+x-25
=>-3x+17=x+9
=>-4x=-8
hay x=2
b: =>17x+16x+27=2x+43
=>33x+27=2x+43
=>31x=16
hay x=16/31
c: =>-2x-3x+51=34+2x-50
=>-5x+51=2x-16
=>-7x=-67
hay x=67/7
e: 3x-32>-5x+1
=>8x>33
hay x>33/8
-3 (2x + 5 ) - 16 < -4 (3 - 2x) => -6x-15-16 < -12 + 8x
=> -6x - 31 < -12 + 8x
=> -6x - 31 +12 - 8x <0
=> -14x - 19 < 0
=> -14x < 19
=> x>-19/14
Chúc bạn học tốt!
\(\dfrac{2x}{15}+\dfrac{2x}{35}+\dfrac{2x}{63}+...+\dfrac{2x}{195}=\dfrac{4}{5}\\ x\cdot\left(\dfrac{2}{15}+\dfrac{2}{35}+\dfrac{2}{63}+...+\dfrac{2}{195}\right)=\dfrac{4}{5}\\ x\cdot\left(\dfrac{2}{3\cdot5}+\dfrac{2}{5\cdot7}+\dfrac{2}{7\cdot9}+...+\dfrac{2}{13\cdot15}\right)=\dfrac{4}{5}\\ x\cdot\left(\dfrac{1}{3}-\dfrac{1}{5}+\dfrac{1}{5}-\dfrac{1}{7}+\dfrac{1}{7}-\dfrac{1}{9}+...+\dfrac{1}{13}-\dfrac{1}{15}\right)=\dfrac{4}{5}\\ x\cdot\left(\dfrac{1}{3}-\dfrac{1}{15}\right)=\dfrac{4}{5}\\ x\cdot\dfrac{4}{15}=\dfrac{4}{5}\\ x=\dfrac{4}{5}:\dfrac{4}{15}\\ x=3\)
Gọi \(D=\dfrac{1}{2}-\dfrac{1}{4}+\dfrac{1}{8}-\dfrac{1}{16}+\dfrac{1}{32}-\dfrac{1}{64}\)
\(2D=1-\dfrac{1}{2}+\dfrac{1}{4}-\dfrac{1}{8}+\dfrac{1}{16}-\dfrac{1}{32}\\ 2D+D=\left(1-\dfrac{1}{2}+\dfrac{1}{4}-\dfrac{1}{8}+\dfrac{1}{16}-\dfrac{1}{32}\right)+\left(\dfrac{1}{2}-\dfrac{1}{4}+\dfrac{1}{8}-\dfrac{1}{16}+\dfrac{1}{32}-\dfrac{1}{64}\right)\\ 3D=1-\dfrac{1}{2}+\dfrac{1}{4}-\dfrac{1}{8}+\dfrac{1}{16}-\dfrac{1}{32}+\dfrac{1}{2}-\dfrac{1}{4}+\dfrac{1}{8}-\dfrac{1}{16}+\dfrac{1}{32}-\dfrac{1}{64}\\ 3D=1-\dfrac{1}{64}< 1\\ \Rightarrow D=\dfrac{1-\dfrac{1}{64}}{3}< \dfrac{1}{3}\)
Vậy \(\dfrac{1}{2}-\dfrac{1}{4}+\dfrac{1}{8}-\dfrac{1}{16}+\dfrac{1}{32}-\dfrac{1}{64}< \dfrac{1}{3}\)
\(\Rightarrow15+4x-2x+145< 0\)
\(\Rightarrow\left(15+145\right)+\left(4x-2x\right)< 0\)
\(\Rightarrow160+2x< 0\)
\(\Rightarrow2x< 0-160\)
\(\Rightarrow2x< -160\)
\(\Rightarrow x< \left(-160\right)\div2\)
\(\Rightarrow x< -80\)
Vậy x < -80
\(\Rightarrow\left(-3\right)\times2x+\left(-3\right)\times5-16< \left(-4\right)\times3-\left(-4\right)\times2x\)
\(\Rightarrow-6x+\left(-15\right)-16< \left(-12\right)-\left(-8x\right)\)
\(\Rightarrow-6x-15-16< \left(-12\right)+8x\)
\(\Rightarrow-6x-31< \left(-12\right)+8x\)
\(\Rightarrow-6x-31+12-8x< 0\)
\(\Rightarrow-6x-8x-31+12< 0\)
\(\Rightarrow\left(-6x-8x\right)-19< 0\)
\(\Rightarrow-14x-19< 0\)
\(\Rightarrow-14x< 0+19\)
\(\Rightarrow-14x< 19\)
\(\Rightarrow x< 19\div\left(-14\right)\)
\(\Rightarrow x< -\frac{19}{14}\)
Vậy \(x< -\frac{19}{14}\)
cảm ơn